Pengaruh Fraud Hexagon Terhadap Manajemen Laba Berdasarkan M-score yang Dimodifikasi - Ramadhanil Hosen; Mayar Afriyenti (Universitas Negeri Padang, 2024)
This research aims to examine the effect of the fraud hexagon on earnings management using a modified M-score. The modified M-score formula in this study comes from research by Narsa et al (2023) using five original ratios and four additional ratios. This research is causality research with a quantitative approach. The data in this research comes from company annual reports obtained from the Indonesian Stock Exchange website and the websites of the companies studied. This research uses a purposive sampling technique and the sample in this research consists of 39 manufacturing companies (food & beverage subsector, chemical subsector, and metals and similar subsector) in 2020-2022. To test the hypothesis, this research uses the logistic regression analysis method. The results of this research show that ineffective monitoring has a positive and significant effect on earnings management. while financial stability, change in auditor, change in director, frequent number of CEO pictures, and projects with government have no effect on earnings management.